“Folk History” of the Battle of Stalingrad (Based on the Materials of the Research Project “Stalingraders in the Battle of Stalingrad”) - Aleksandr A. Ogarkov; Elena V. Ogarkova; Igor O. Tyumentsev (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2018)
In 2012–2013, a project of high social significance, novelty, and a scientific challenge was implemented in Volgograd. The goal of the project was to prepare the manuscript of a biographic encyclopedia “Stalingraders in The Battle of Stalingrad”. The database of sources that have never been published consists of materials of 80 museums and archives of Volgograd and 30 municipal subjects of the Volgograd region. The novelty of the project consists in the fact that it constitutes the first case of biographic and prosopographic research on the local aspect of the battle. The manuscript includes more than 5 000 biographic articles. The project bears high social significance since it generalizes the data on people for whom the Battle of Stalingrad was the battle for their “little Motherland”. Introducing the biographies of Stalingraders into the research has a memorial goal. The research problems under the project are also important. The new research paradigm, defined as “human dimension of war” leads to collecting a huge amount of empirical data. The idea of the project, as well as the difficulties in its completion, are very characteristic for the current stage of Russian research of the Great Patriotic War. Data collection, large-scale search projects on war cites, interest to all new resources go beyond the professional society of historians. However, generalizing this material, and verifying sources remains within the competence of experts. The historians must evaluate the conceptual idea of quantitative methods in studying war history of Russia. In the project, the quantitative methods lead to supported conclusions about close interaction of the front and the rear at the level of everyday life; they remove the stereotypes of exclusively sacrificial role of civilians in the Battle of Stalingrad. The project overcomes the one-sided look at the war generation as to the “chosen” one, having a special part in history; this allows the return to the historic justice in the space of memory.